Proceedings of the 26th Annual International ACM SIGIR Conference on Research and Development in Informaion Retrieval 2003
DOI: 10.1145/860435.860453
|View full text |Cite
|
Sign up to set email alerts
|

Using terminological feedback for web search refinement

Abstract: Although interactive query reformulation has been actively studied in the laboratory, little is known about the actual behavior of web searchers who are offered terminological feedback along with their search results. We analyze log sessions for two groups of users interacting with variants of the AltaVista search enginea baseline group given no terminological feedback and a feedback group to whom twelve refinement terms are offered along with the search results. We examine uptake, refinement effectiveness, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(131 citation statements)
references
References 13 publications
1
130
0
Order By: Relevance
“…The first studies were focused in the functionality of the search engines, describing query patterns in Altavista (Silverstein, Henzinger, Marais, & Moricz, 1998;Silverstein, Marais, Henzinger, Moricz, 1999;Anick, 2003), Excite and Alltheweb (Jansen & Spink, 2006) and Yahoo! (Teevan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The first studies were focused in the functionality of the search engines, describing query patterns in Altavista (Silverstein, Henzinger, Marais, & Moricz, 1998;Silverstein, Marais, Henzinger, Moricz, 1999;Anick, 2003), Excite and Alltheweb (Jansen & Spink, 2006) and Yahoo! (Teevan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several Web search engines have begun offering short lists of search refinement suggestions to encourage the interactive narrowing of query result sets. Anick (2003) reports on the results of several log-based studies of user interaction with the AltaVista 4 Prisma assisted search tool. In particular, they study the degree and nature of user uptake of the feature, as well as the conditions and effectiveness of its use within information seeking sessions based on an analysis of anonymous user activity logs from the AltaVista search site.…”
Section: Query Suggestionmentioning
confidence: 99%
“…Among all the papers reviewed in this work, only a few explicitly claim the need of a combination of different sources of evidence: Mahoui and Cunningham (2000) write that further studies, including interview-based examinations of small groups of users, are required to complete their work; Anick (2003) needs laboratory tests or questionnaires to answer more complex questions. Koch et al (2004) found that a thorough log analysis can provide deeper understanding of the services and they may offer useful hypotheses for advanced user studies.…”
Section: Combining Different Streams Of Log Datamentioning
confidence: 99%
“…In spirit, our super phrases are similar to those generated by Anick from top-ranked documents and past queries in the Prisma system [2], and by Gauch from a back-of-the-book index in an expert system for searching [18]. The hyperindex meta-search engine described by Bruza and Dennis [7] appears to be closest to our approach of narrowing and widening.…”
Section: Generalization and Specialization In Proximity Searchmentioning
confidence: 99%
“…2 For each of these subphrases there are two orderings. The subphrase AB is covered by four minimal sequences in d:…”
Section: Proximal Subphrasesmentioning
confidence: 99%